Tindakan Do Not Resuscicate Pasien Terminal di Instalasi Gawat Darurat Rumah Sakit Dalam Perspektif Hukum Pidana - nur fadillah; Ukas Ukas (LPPM Universitas Putera Batam, 2025)
A medical order called Do Not Resuscitate (DNR) tells you not to perform Cardiopulmonary Resuscitation (CPR) on a patient based on clinical, ethical, moral, and legal considerations. DNR masih menjadi masalah kontroversial di beberapa negara dan sering dikaitkan dengan euthanasia passive. Dalam konteks perlindungan hukum bagi dokter di hospitals, tujuan dari penelitian ini adalah untuk menyelidiki status hukum DNR. The study uses both normative and empirical legal techniques, using statutes, legal principles, doctrines, and interviews with important informants like the Head of the Medical Committee, medical specialists, and the Chairman of the Indonesian Medical Association (IDI) of Bintan Regency. Hasil menunjukkan bahwa DNR memiliki fondasi hukum yang jelas. Ini ditunjukkan oleh Peraturan Nomor 37 Tahun 2014 dari Ministry of Health tentang Penentuan Kematian dan Penggunaan Organ, serta Peraturan Nomor 37 Tahun 2014. mengenai Persetujuan Tindakan Medis 290/MENKES/PER/III/2008. As stated in Article 4, legal protection for physicians in the implementation of DNR is provided preventively through informed consent and repressively in emergency situations. Physicians rely on these two rules to make moral and legal decisions about ending or postponing life-sustaining treatment.